(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of sports implementation time, namely morning and evening, on the VO2Max of futsal athletes at SMA Negeri 4 Makassar. Formulation of the problem What is the difference in the VO2Max value of futsal athletes at SMA Negeri 4 Makassar who exercise in the morning compared to those who exercise in the evening? This research uses a quantitative approach with experimental methods. The research sample consisted of 10 futsal athletes who exercised in the morning and 10 athletes who exercised in the evening. The data obtained were analyzed using statistical tests with a significance value of P